Impact of Long Dry Season on Bean Characteristics of Robusta Coffee (Coffea canephora) - Ucu Sumirat (Indonesian Coffee and Cocoa Research Institute, 2008)
Bean characteristics in Robusta coffee (Coffea canephora) should be taken into considerations in coffee breeding. Beside genetic factor, environment has been known as an important factor in the formation and change of composition of bean characteristics. This research aimed to find out the effect of long dry season on changes of bean characteristics. The population observed consisted of 277 genotypes originated from reciprocal crossings of three parental namely BP 409, BP 961 and Q 121. Observation was conducted in Kaliwining Experimental Garden of ICCRI in Jember, East Java during two years with different drought intensity i.e. 2005—2006 and 2006—2007 production years. The result showed that long dry season decreased the range value of population of normal beans, pea beans and triage beans, and followed by decreasing in the mean value except for normal beans. Long dry season also influence the change of value range of empty bean to higher proportion, and followed by increasing in the mean value. Distribution pattern of normal beans tend in to remain at high proportion, in contrast to those of pea and triage beans. In other side, long dry season tended to change distribution pattern of empty beans to at high proportion. Correlation analysis among beans characteristics showed that normal beans had negative correlations with pea beans and empty beans. Pea beans had a positive correlation with empty beans. Long dry season decreased proportion of pea bean and triage bean, in contrast to those of empty beans. Increasing proportion of empty bean was caused by failure of growth to normal bean under stress condition. Key words : Coffee canephora, bean characteristics, long dry season, variation, correlation, composition.